Pengaruh Disiplin Kerja, Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Pegawai di Universitas Medan Area - Agus Salim Harahap (ARBITRASE: Journal of Economics and Accounting, 2021)
This study was conducted to determine the effect of work discipline, work environment and compensation on employee performance at the University of Medan Area. This study uses a quantitative method with a sample of 50 employees from various units using the Multiple Linear Regression Analysis tool. The results of this study are that there is an insignificant effect between Work Discipline on Employee Performance. There is an insignificant effect between the Work Environment on Performance. There is a significant influence between compensation on employee performance. Simultaneously there is a significant influence between Work Discipline, Work Environment and Compensation together on employee performance. The coefficient of determination (Rsqure) is 0.575 and the value (Adjusted R Square) is 0.547 or 54.7% meaning the variables (Work Discipline, Work Environment and Compensation) ), the study was able to explain the employee performance by 54.7% while the remaining 45.3% was influenced by other variables outside this study such as leadership style variables, work motivation, job satisfaction, and work climate.